Chemical Structure and Immune Activation of a Glucan From Rhizoma Acori Tatarinowii - Zhang, Wuxia; He, Jiaqi; Hu, Yihua; Lu, Jingwu; Zhao, Jinzhong; Li, Peng (Frontiers in Nutrition, 2022)
Rhizoma Acori Tatarinowii is a traditional Chinese herb used to treat depression and coronary heart disease. Studies on its active components mainly focus on small molecular compounds such as asarone and other essential oil components, while the large molecular active components such as polysaccharides are ignored. Here, we aim to study the chemical structure and immune activation of polysaccharides from Rhizoma Acori Tatarinowii. In this study, a polysaccharide (RATAPW) was isolated and purified by DEAE-52 cellulose and Sephadex G-100 column chromatography from alkali extraction polysaccharide of Rhizoma Acori Tatarinowii. The average molecular weight of RATAPW was 2.51×104 Da, and the total carbohydrate contents of RATAPW were 98.23% ± 0.29%. The monosaccharide composition, methylation and NMR analysis results displayed that the polysaccharide was α-1,4-glucan with short α-1,6 branches. Immunofluorescence assay and inhibitor neutralization assay indicated that RATAPW could promote the TNF-α production of RAW264.7 macrophage through the NF-κB molecular signaling pathway. Treatment with 200 μg/mL RATAPW enhanced a 38.77% rise in the proliferation rate of spleen lymphocytes. RATAPW also enhances ConA-induced T cells and LPS-induced B cell proliferation in a dose-dependent. Our study lays a foundation for the discovery of natural polysaccharide immune modulators or functional food from Rhizoma Acori Tatarinowii.